2016
DOI: 10.1111/disa.12220
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the strategic antecedents of agility in humanitarian logistics

Abstract: This study investigates the strategic antecedents of operational agility in humanitarian logistics. It began by identifying the particular actions to be taken at the strategic level of a humanitarian organisation to support field-level agility. Next, quantitative data (n=59) were collected on four strategic-level capabilities (being purposeful, action-focused, collaborative, and learning-oriented) and on operational agility (field responsiveness and flexibility). Using a quantitative analysis, the study tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Previous studies have acknowledged the relevance of the combined effect of SCAG and SCRES on supply chain performance (Carvalho, Azevedo, and Cruz-Machado 2012). However, in the humanitarian context most of the existing studies have either examined the effect of SCAG (L'Hermitte et al 2017;Oloruntoba and Gray 2006;Oloruntoba and Kovacs 2015) or resilience (Tabaklar et al 2015) on supply chain performance. We have grounded our debate in the view that SCAG and SCRES are two dynamic capabilities of supply chain.…”
Section: Implications For Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have acknowledged the relevance of the combined effect of SCAG and SCRES on supply chain performance (Carvalho, Azevedo, and Cruz-Machado 2012). However, in the humanitarian context most of the existing studies have either examined the effect of SCAG (L'Hermitte et al 2017;Oloruntoba and Gray 2006;Oloruntoba and Kovacs 2015) or resilience (Tabaklar et al 2015) on supply chain performance. We have grounded our debate in the view that SCAG and SCRES are two dynamic capabilities of supply chain.…”
Section: Implications For Theorymentioning
confidence: 99%
“…Lee and Rha 2016). Following Lee and Rha's (2016) arguments, we posit that HSC organizations can pursue simultaneously SCAG, which will enable the humanitarian organizations (HOs) to respond to respond to disaster-affected victims with right humanitarian aids in right time (Charles, Lauras, and Van Wassenhove 2010;L'Hermitte et al 2017) and SCRES, will further help to sustain the humanitarian efforts over the time despite of high degree of environmental uncertainties arising from cultural diversity among humanitarian actors and the political risk (Day et al 2012) (see Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…According to the SC learning literature it can be emphasized that the "being collaborative" and "being purposeful" can play a significant role in learning process (Gibson et al, 2016;Lambrechts et al, 2012;Willis et al, 2016;Yang et al, 2019). The role of this dynamic capability has an important place in the SCM and DCs literature (L'Hermitte et al, 2017;Li et al, 2018;Yang et al, 2019). However, despite the importance of it, the evidence shows that HOs' efforts can be regarded insufficient given the fact that it is not applied to its full potential and there is no integrated and formal mechanism established for the learning practices (L'Hermitte et al, 2016).…”
Section: Dynamic Capabilities In Humanitarian Scmmentioning
confidence: 99%
“…Torabi pointed out that strategic planning is the basis for making correct decisions [36]. L'Hermitte believed that sustainable strategic management should include an overall strategy and updated decisions based on phased disasters [37]. John suggested that humanitarian supply chain managers should confirm the source of supplies and conduct timely inspections of donated materials [38].…”
Section: Identification Of Criteria and Indicatorsmentioning
confidence: 99%